SOSIALISASI EDUKASI BAHAYA TOXOPLASMOSIS TERHADAP KELOMPOK PEMUDA USIA PRODUKTIF DI KOTA KUPANG - Larry R. W. Toha; Diana Agustiani Wuri; Annytha I. R. Detha; Novalino H. G. Kallau; Katarina O. Jebe; Deswandi W. S. Berry; Kefin E. Tahun; Diana R. N. A. Awa; Elise M. Ballo; Gracela U. Ara; Maria I. Tulasi; Andianus F. Surak; Maria M. Kewa (Universitas Nusa Cendana, 2021)
Toxoplasmosis is a disease of vertebrate animals and it is capable of being transmitted to humans (zoonosis). Toxoplasmosis is caused by the protozoan parasite Toxoplama gondii. Cats are the definitive host of T. gondii where this parasite will enter the cat's body through what it eats such as rats, raw meat, or water that is contaminated with oocysts of the T. gondii parasite. This condition is generally experienced by stray cats or domesticated cats which are often given raw meat. The purpose of this activity is to increase public understanding of the dangers of toxoplasmosis and how to prevent and anticipate the spread of toxoplasmosis in Kupang City. The method used in this community education was through presentation and discussions about the danger of toxoplasmosis. To measure the level of understanding of the participants about the dangers of toxoplasma, a questionnaire is given at the beginning and at the end of the activity. A total of 38 participants from the productive youth groups in Kupang City were involved in this activity. The result of this activity shows that the public is increasingly educated about toxoplasmosis and how it is transmitted.